Conceptual Analysis of Pro-Environmental Behavior: A Bibliometric Approach - Eryesil, Kemalettin; Ozturk, Resul; Ozturk, Mehtap (Int Journal Contemporary Economics & Administrative Sciences, 2025)
This study provides information on the conceptual and historical evolution of pro-environmental behavior (PEB) through bibliometric analysis. This study examines 4740 articles in the Web of Science (WOS) database published between 1981 and 2024. The development of the PEB examines using performance and science mapping techniques and co-authorship, co-occurrence, citation, and co-citation analysis using the VOSviewer program. When the PEB was evaluated, it was determined that the concept was first expressed as conservation behavior, and the term pro-environmental was used in different ways, such as environmentally friendly, environmentally responsible, sustainable, green, and recycling. It was observed that PEB was first used in the literature in 1981. It has also been determined that PEB has been discussed within the framework of different theories, including the Norm Activation Model, the Theory of Planned Behavior, and the Value-Belief-Norm Theory. However, there has been a gradual increase in publications since 1981, and the literature has been in a rapid growth phase in recent years. In this context, PEB is a widespread phenomenon that has attracted attention in the literature in recent years. Over the years, PEB has evolved into consumer engagement, corporate greening, corporate social responsibility, employee green behavior, environmental consciousness, environmental management, and environmental sustainability. Within the scope of the study, the conceptual evolution of PEB over the years has been evaluated and suggestions for future studies have been made.
Keywords: Pro-Environmental Behavior; Conceptual Analysis; Bibliometric Analysis